USE OF Azospirillum brasilense IN SINGLE CORN AND INTERCROPPING WITH Brachiaria ruziziensis - Veronezi, S. D. F.; Ribeiro, L. M.; Ceccon, G. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The research had as objective to evaluate the development of single maize and intercropping with B. ruziziensis, after applications of Azospirillum brasilense. The experiment was conducted in Dourados, municipality, Mato Grosso do Sul state. The experimental design was DBC in subdivided plots with four replications. The main plots were maize single and intercropped; in the subplots the applications of A. brasilense: T1) P-K (control); T2) P-K + A. brasilense foliar; T3) P-K + A. brasilense in the seed; T4) N-P-K; T5) N-P-K + A. brasilense foliar; T6) N-P-K + N in coverage; T7) N-P-K + A. brasilense in the seed; T8) N-P-K + A. brasilense in seed + N in cover. During flowering, plant height, stem insertion, stalk diameter, leaf area index, chlorophyll a, b and total were evaluated, and the dry maize biomass of 100 grains, grain per spike and grain yield were evaluated in the harvest. The N, P, K, Ca, Mg, S, Cu, Fe, B, Mn and Zn were evaluated in the green leaves, grains and dry mass off plant. The data were submitted to analysis of variance and the means were compared by the Tukey's test (p<0.05). The application of A. brasilense stimulated the growth of the safflower corn, regardless of the mode of cultivation. Utilization of N and A. brasilense at sowing resulted in better vegetative growth of corn without interfering with grain yield.